A Study of the Association Between IL-17 and HOMA-IR in Iraqi Type 2 Diabetic Patients - Abbas, Khetam M.; Alaaraji, Shakir .F. T.; Al–Shawk, Refif Sabih (Iraqi Journal of Science, 2020)
Type 2 Diabetes Mellitus (T2DM) is the furthermost common form of DM which is identified by hyperglycemia, insulin resistance, and relative insulin deficiency. This study aims to detect the role of interleukin-17 (IL-17) in patients with T2DM compared with the healthy control and to investigate the relationship between IL-17 and insulin resistance. The study involved 50 Iraqi T2DM patients, randomly selected with an age range of 33-71 years .For the purpose of comparison, 30 Iraqi healthy persons with an age range of 33-71 years were also included. Patients and control groups were characterized in terms of gender, age, body mass index (BMI), homeostatic model assessment-insulin resistance(HOMA-IR),fasting serum glucose (FSG) and lipid profile. The means of IL-17 (368.45 vs. 128.50 pg/ml), HOMA-IR (7.94vs. 2.14),FSG (152.82 vs. 81.53 mg/dl), fasting serum insulin (FSI) level (19.37 vs. 10.71 μIU/ml), Triglycerides (TG), High Density Lipoprotein (HDL),and Very Low Density Lipoprotein (VLDL) were significantly higher in T2DM patients as compared to controls. While, levels of Total Cholesterol (TC)and Low Density Lipoprotein (LDL)showed non-significant differences. In conclusion, IL-17 seems to play a significant role as a risk factor for the development of T2DM.Also, higher (HOMA-IR) gives rise to a hyperglycemic state and is a major risk factor for the development of T2DM.